2019
DOI: 10.1371/journal.pone.0221712
|View full text |Cite
|
Sign up to set email alerts
|

Burden and determinants of malnutrition among pregnant women in Africa: A systematic review and meta-analysis

Abstract: Background Malnutrition in pregnancy remains unacceptably high across all regions of Africa though promising progresses have been made globally. Primary studies might not be sufficient to portrait a comprehensive picture of malnutrition during pregnancy and its main risk factors. Therefore, we intended to review the burden of malnutrition, for this specific review implies to protein energy malnutrition, during pregnancy in Africa to present its magnitude and determinant factors. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
92
6
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 95 publications
14
92
6
6
Order By: Relevance
“…Our result is consistent with those of other three studies carried out in other parts of Ethiopia 19.8%, 19.5% and 24% (23,31,32). It is also consistent with ndings of a study done in south Sudan and a systemic review in Africa reported 18.9% and 23.5% respectively (20,33) . On the other hand, our nding is higher than those of studies did in three areas of Ethiopia and Madagascar reported 16.2%, 14.4%, 9.2% and 9% respectively (22,(34)(35)(36).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result is consistent with those of other three studies carried out in other parts of Ethiopia 19.8%, 19.5% and 24% (23,31,32). It is also consistent with ndings of a study done in south Sudan and a systemic review in Africa reported 18.9% and 23.5% respectively (20,33) . On the other hand, our nding is higher than those of studies did in three areas of Ethiopia and Madagascar reported 16.2%, 14.4%, 9.2% and 9% respectively (22,(34)(35)(36).…”
Section: Discussionsupporting
confidence: 93%
“…In developing nations including Ethiopia, burden of maternal and child undernutrition is very high. The prevalence of maternal undernutrition in Africa including Ethiopia found between 11%-36% (20)(21)(22)(23)(24)(25)(26)(27). The most acceptable explanation for this wide variation is likely to be the fact that contextual factors are major determinants of maternal undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Even they may not have enough monthly income for good food diversity and [69]. This gure is in line with systematic review done in Africa and studies done in Pakistan and Bangladesh [17,61,66].…”
Section: Discussionsupporting
confidence: 81%
“…The nding of this review was higher than ndings of systematic review done in Africa, studies done in Democratic Republic of Congo, Lebanon, Sudan and Sri Lanka which was 23.5%, 14%, 10.2%, 15% and 5.5% respectively [61][62][63][64][65]. But, this nding was lower than results of studies conducted in Bangladesh, South India and Kenya which was 59%, 51% and 31.7% respectively [66][67][68].…”
Section: Discussioncontrasting
confidence: 62%
“…This study investigated the prevalence and factors associated with underweight among lactating Ugandan women aged between 20 to 49 years. Based on the anthropometric measurement of body mass index, 8.2% (95% CI: 7.0-10.0), of lactating women were underweight with BMI less than 18.5 kg/m 2 which prevalence is below the standard acceptable malnutrition rate of 10% (23) .Of the 8.2%, 3.6% were severely underweight, 20.5% were moderately underweight and 75.9% mildly underweight. This prevalence is lower than studies conducted among lactating women in Ethiopia (5,8,12), rural Vietnam (24) and India (25) but higher than a study done in Nigeria (9).…”
Section: Discussionmentioning
confidence: 99%